Conceptualising Local Ownership as 'Reflexive Cooperation': The Deferral of Self-government to Protect 'Unequal' Humans? - Pol Bargués Pedreny (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2015)
This article analyses how the concept of `local ownership' has been employed within policy frameworks in the context of peacebuilding since the late 1990s. It identifies the paradox that lies in the increasing willingness to transfer ownership to the local population and the also explicit assumption that self-determination and self-government have to be avoided in democratisation and post-conflict situations. It is argued that it is important to investigate the paradox, the fact that ownership and self-government have opposed connotations within contemporary frameworks of peacebuilding, because in the literature this position is not seen as being contradictory. Far from being seen as a strategy containing an irreconcilable paradox, local ownership is conceptualised so that it resolves at the same time two problems at the core of international governance settings: it limits the international administrators' intrusiveness in national affairs and avoids the risk of giving too much responsibility to local authorities. While it is presented as a progressive strategy on all fronts, the conclusion of this article is that the concept of ownership, as it has been interpreted by the discourses of peacebuilding analysed here, has been of little value to post-conflict societies and, furthermore, it has denied their moral and political autonomy. This denial, disguised as a discourse that promises to embrace difference, is particularly flawed because it seems to permanently defer equality between internationally supervised populations and the rest of sovereign nations.
urn:nbn:de:hbz:464-20160127-143334-4
Keywords: 320; Peacebuilding; local ownership; self-government; hybridity; reflexive cooperation